BTEC HNC HND Business / Core Module Three: Managing People and Activities (Bpp Publishing, 1996)
This Text on Market Relations has been written specifically for Core Module 1 of the BTEC HNC in Business. It gives full coverage of the BTEC Guidelines for learning outcomes and suggested content. Preface, BTEC Guidelines for Core Module 3, Study Guide, Managing People, Perspectives on Management, Management Style, Individual Behavior at Work, Motivation, Interpersonal Behavior at Work, Teams, Monitoring Performance, Enhancing Performance, Problem-Solving, Managing Activities, Planning and Organizing, Managing Time, Managing Projects, Communication, Co-ordination, Review and Monitoring, Constraints on Management, Answers to Assignments, Glossary, Index, Review Form.